Python – A comprehensive yet free programming language for statisticians. Issue 2 (3rd March 2016) - Shukla, Xitij U.; Parmar, Dinesh J.
Abstract: This article describes Python - a promising, popular, free programming language. Various tools for computation, analysis and visualization of data especially for the statisticians, available under the Python are briefly discussed in a tutorial centric approach.